Integrating Natural and Social Aspects in Shaping the Distribution of Village Service Facilities in Singaraya Village, Sambas Regency - Roli, Roli; Anasa, Putri Tipa; Juniarsih, Sri; Haliva, Alya; Ririn, Ririn; Mulia, Desti; Christanto, Ludovicus Manditya Hari (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
Settlements in Singaraya Village, Semparuk District, Sambas Regency, have undergone changes in pattern along with social, economic, and environmental dynamics. This study aims to analyze settlement patterns and the factors that influence them. The methods used were field surveys, direct observation, and spatial analysis using GIS software. Primary data were obtained through interviews and observations of residents and the physical conditions of the village, while secondary data were supported by topographic maps and demographic data. The results show that settlement patterns in this village are dominated by settlement patterns based on following rivers and roads that are influenced by factors such as road accessibility, land availability, and local culture. These findings indicate that infrastructure development and village development must consider socio-cultural factors to support sustainability and spatial balance. The conclusion of this study emphasizes the importance of integrating physical and social aspects in managing village settlement patterns in the future.